The Use of Clustering Technique to Increase the Ability of the First Year Students at SMAN 9 Pekanbaru in Writing Descriptive Text - Riska Fitriyani Fitriyani; Raida Johar Johar; Maisrul ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrack: The research is a classroom action research that was conducted based on the problem occurred at the first year of SMA Negeri 9 Pekanbaru, namely the students were lack of practice in writing descriptive text and this situation made them got poor score in test. Therefore, this research was aimed at studying the improvement on the ability of the first year students of SMA Negeri 9 Pekanbaru in writing descriptive by using Clustering technique. Besides, this research was also intended to identify which components of writing are mostly improved after being taught by using Clustering technique. The participants were 34 students from X2 class of SMA N 9 Pekanbaru. This research was conducted in 2 cycles. The data collection technique were obtained through (1) Writing test was done to measures students’ achievement, (2). Observation sheet was applied to know the students’ activities during teaching and learning process. The research findings can be briefly explained as follow:  First, the students’ writing ability could be improved by using Clustering technique. Before the research was done, the average score of the students’ listening was only 43.92. After giving the treatment in cycle 1, the score has been improved to 67.32. In cycle 2, it increased up to 78.01. Second, based on the students observation sheet, it showed that the students’ activeness during the treatments by using Clustering technique also improved. From the score of writing test and the students and teacher observation sheet showed that the used of Clustering technique made the teaching process more effective and it also helped students improved their writing ability.   Keyword: Clustering technique, Students’ Writing Ability, and Descriptive